2009
DOI: 10.1080/19438150903090491
|View full text |Cite
|
Sign up to set email alerts
|

Traditional knowledge in international forest policy: contested meanings and divergent discourses

Abstract: 'Traditional knowledge' gained political space in international environmental policy up until the early 1990s as a result of three areas of growing concern: environmental sustainability, indigenous peoples' rights and the commercial potential of traditional knowledge. Prominent at the 1992 United Nations Conference on Environment and Development (UNCED), traditional knowledge was a key term in the emerging discourse alliance on sustainable development. This article traces the convergence and divergence of disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In international environmental politics, the indigenous speaker position gained legitimacy when Euro-Americans started “to speak of their societies as ‘information societies’ and of ‘knowledge’ as industrial capital … and when genetic and biological material come to be treated as information resources” (Strathern 1999, cited in Muehlebach, 2001, p. 417). Thereafter, indigenous people have been intersubjectively constructed as owners of valuable knowledge for attaining sustainable development (Agrawal, 1995), managing biodiversity (Newing, 2009), and contributing to the success of emerging mechanisms to address climate change (Wallbott, 2014). Although there are various indigenous speaker positions embedded in specific sociohistorical settings, in the international environmental arena, the indigenous speaker position is characterized by a “fairly unitary argumentative thrust” (Muehlebach, 2001, p. 416).…”
Section: Discussionmentioning
confidence: 99%
“…In international environmental politics, the indigenous speaker position gained legitimacy when Euro-Americans started “to speak of their societies as ‘information societies’ and of ‘knowledge’ as industrial capital … and when genetic and biological material come to be treated as information resources” (Strathern 1999, cited in Muehlebach, 2001, p. 417). Thereafter, indigenous people have been intersubjectively constructed as owners of valuable knowledge for attaining sustainable development (Agrawal, 1995), managing biodiversity (Newing, 2009), and contributing to the success of emerging mechanisms to address climate change (Wallbott, 2014). Although there are various indigenous speaker positions embedded in specific sociohistorical settings, in the international environmental arena, the indigenous speaker position is characterized by a “fairly unitary argumentative thrust” (Muehlebach, 2001, p. 416).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that a discourse acquires hegemony if it is integrated into institutions and organisational practices (Hajer 1993, Predmore et al, 2008Newing, 2009;Mert, 2009;Leipold, 2014). This was particularly evident for the managerial discourse, which is deeply embedded in traditional forestry practice, organisational structures and nationallevel regulations.…”
Section: Discussionmentioning
confidence: 99%
“…In the end, EU legislation legitimised the Polish government's final decision and led to stricter protection of the Białowieża Forest. However, the resulting situation of competing concepts being enshrined in a single institution (Newing, 2009) warrants further study regarding its effects on the development of the conflict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discourses around the appropriate role of IPLCs in conservation were always contested—amongst academics, conservationists, and social movements (Agrawal & Gibson, 1999; Ciplet, 2014; Newing, 2009). And, even as the exact meaning of IPLC involvement in these new conservation calls remains vague, and the direct support to these groups quite limited (Rights and Resources Initiative and Rainforest Foundation Norway, 2022), the dramatic shift in mainstream discourse regarding their importance reflects the long‐standing effort of IPLCs to affect conservation governance processes from the local to the global (Rodrigues, 2015; Sauls, 2020; Wallbott, 2014).…”
Section: Introductionmentioning
confidence: 99%